Efektivitas Sighat Ta‘liq Sebagai Instrumen Perlindungan Hak Istri dalam Sistem Hukum Perkawinan di Indonesia - Asenda Hella Purwaninda (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2026)
This study aims to analyze the effectiveness of sighat ta‘liq as an instrument for protecting wives’ rights within the Indonesian marriage law system and to explore efforts to strengthen its reformulation. The main issues examined include the legal status of sighat ta‘liq, its implementation in marriage practices and court proceedings, its effectiveness in safeguarding wives’ rights, and the factors influencing its effectiveness. This research employs a normative juridical approach through the analysis of primary, secondary, and tertiary legal materials, which are then examined qualitatively. The findings indicate that sighat ta‘liq has the potential to serve as an instrument for protecting wives’ rights; however, its effectiveness remains limited due to non-operational legal substance, formalistic law enforcement, and the patriarchal culture within society. Normative reformulation, capacity building for legal apparatus, and public legal education are necessary to optimize the function of sighat ta‘liq. This study contributes theoretically by strengthening the understanding of a marriage law system that is responsive to women’s rights, and practically by informing family law policy, court guidelines, and legal literacy for prospective spouses. These findings can be applied to promote more effective protection of wives’ rights through the integration of sighat ta‘liq into national regulations and judicial practice.